Honey as a Medium of Non-Surgical Periodontal Therapy - Zainab Javaid, Usman Rashid, Sarmad Saif, Laraib Qamar, Maaz Ahmad, Shahab Rafiq, Marij Hameed, Muhammad Tahir Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Gingivitis is an infection caused by plaque and calculus accumulation. Gingivitis if not treated progress to periodontitis, a more advanced form of gum disease. Periodontal disease was the world's 11th most frequent disease in 2016 according to the World Health Organization. Surgical as well non- surgical periodontal therapies are carried out for periodontal disease treatment. Debridement of supra-gingival and sub-gingival calculus, along with instructions about oral health care methods are the basis of traditional non-surgical periodontal therapy (NTPS). Honey is beneficial to oral health, particularly in the cure of plaque formation, gingiva inflammation, periodontitis and odor control. Honey has antibacterial activity and is effective against both gram-positive as well as gram-negative bacteria. Honey's antibacterial and anti-inflammatory characteristics can promote the granulation tissue formation and enabling damaged cells to be regeneration. Materials And Method: This review followed the guided framework from the approach of Arksey and O'Malley for the scoping review (2005). The methodology was chosen because it has a five-stage framework. Exclusion & inclusion criteria were made and 60 articles were selected. Articles were searched from the PubMed, Google Scholar and other search engines. Results: Based on the data retrieved we concluded that honey can be used as a medium for non-surgical periodontal therapy. Honey have antibacterial and anti-inflammatory properties due high osmolarity, acidic nature and hydrogen peroxide as well non-peroxide components of honey and is used by many researcher for cure of periodontal disease but still there is not very strong evidence that locally given honey affects periodontal tissue healing. Despite this, all of the pockets had a good periodontal repair. Honey's efficacy in the treatment periodontal disease is still not well established and still questionable. To substantiate these findings from the literature, more research will be required.